Adoption of Competitor Focused Accounting Methods in Selected Manufacturing Companies in Nigeria - Rita, Chiekezie Njideka; Amaechi, Egbunike Patrick; Nwekemezie, Odum Austin (Asian Journal of Economic Modelling, 2014)
This study-examined the extent of adoption of competitor focused accounting (CFA) in selected manufacturing firms listed on Nigerian Stock Exchange with a view to establishing whether there are differences in financial performance of the firms. The study is descriptive in nature and uses survey techniques. Accordingly, two-hundred and twenty four (224) key respondents in the Nigerian manufacturing industry were surveyed. This is complimented with secondary data collected from annual accounts and reports of fifty six (56) manufacturing companies listed in the Nigerian stock exchange. In addition to descriptive statistics, analysis of variance (F- Ratio) and scheffes’ (fs) test were used in analyzing collected data. The result of the study revealed that 14 companies representing (25%) were non-adopters of competitor focused accounting methods, 36 (64.3%) were partial adopters while 6 (10.7%) were full adopters. In addition, the mean financial performance of full adopters of CFA methods was 25.1 greater than that of partial adopters and also 45.71 greater than non-adopters. This shows a large difference. On the other hand, partial adopters’ mean financial performance was 20.61 greater than that of non adopters of CFA methods. However, this study proves that the practice of CFA in Nigerian manufacturing companies is still below average and the necessity to improve this situation is the current challenge. Manufacturing firms in Nigeria should give priority to strategic management accounting and it sub-divisions especially CFA in other to enhance its competitive edge over competitors.